Seals and pack ice : contrasting behaviours in response to changing ice conditions in the Gulf of St. Lawrence - Cusson, Pier-Olivier; Pelletier, Fanie (Université de Sherbrooke., 2023)
Abstract : "Seasonal ice floes are vast expanses of temporary ice that float on the surface of the oceans in polar and subpolar regions. They play an important role in regulating the planet's climate and are an important habitat for many animal species. They form in winter when seawater cools to the point where small ice crystals form and coalesce into increasingly thick ice masses. Under ideal conditions, these ice floes can reach a thickness of over one metre and extend over several thousand square kilometres. However, the freezing point of salt water is lower than that of fresh water (-1.9 °C compared to 0 °C), which is why pack ice is particularly sensitive to water warming. In recent decades, their gradual disappearance has become a constant reminder of the impacts of climate change. [.]"